Índice de vagas preenchidas pelas eleições universitárias locais do campus São Borja da Unipampa: relatório sobre provimento de órgãos colegiados por processos eleitorais - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The objective of this report is to present the Index of Vacancies Filled (IVP) by the Local University Elections of the São Borja Campus of the Federal University of Pampa (UNIPAMPA), an indicator that seeks to measure the efficiency of local electoral processes conducted by the Unit. This document also presents research in which the aforementioned indicator was used. The study proposes to support evidence-based institutional assessment with technical-scientific elements and inputs, delimited to the degree of engagement and participation in local electoral processes concluded within the scope of UNIPAMPA's São Borja Campus. At the same time, the systematization and dissemination of statistical data contained in this report reflect accountability actions and promotion of transparency on the part of CEL in relation to the work carried out in the five-year period 2018-2022. Of the seven local electoral processes concluded in the period, only one of them adopted the traditional methodology of in-person elections, using physical ballot boxes and paper ballots. The others were carried out using digital technologies, an online consultation model used in UNIPAMPA university elections. The research revealed an average IVP of around 47%, with the rates of the electoral processes analyzed fluctuating in the range of half of the vacancies filled by each of them. As for the indices calculated by segment of the university community (teacher, student and administrative technician), they vary between each other and throughout the period considered. The index that proved to be more stable and with the best average performance was that of the student segment. The teaching staff was the only one of the three categories that achieved 100% filling of representative vacancies, having also repeated the optimum occupation point on two occasions. The IVP of the technical-administrative segment never reached, during the researched period, the occupation of half of the representations made available to the Campus staff.
Keywords: Universidades e faculdades – Eleições; Ensino superior - Administração; Eleições - Universidade Federal do Pampa; Transparência na administração pública; Governança pública; CNPQ::CIENCIAS HUMANAS